Stress Field of the Earth's Crust - Zang, Arno. (Springer Netherlands : Imprint: Springer, 2010)
This book about rock stress is suitable for students in geosciences and rock engineering, who need to broaden their horizons about the Stress Field of the Earth’s Crust. The book covers the topic so that geosciences students will be able to grasp the Cauchy Stress Principle without fear of matrix transformations in an exercise. Students interested in mathematics, physics and engineering will learn how strain gauges are used to obtain in-situ stress by the overcoring method. Leading edge technology in determining rock stress like quadruple packer and the Kaiser effect are presented together with classical methods like hydraulic fracturing. Borehole techniques (breakouts) and core-based methods (anelastic strain recovery) are illustrated. With respect to stress data, we choose to present the scientific ultra-deep drilling project KTB (Germany), the excavation for nuclear waste disposal at Olkiluoto (Finland) and the drilling into a seismic active fault zone at SAFOD (USA). Stress compilations viewed by the World Stress Map project are presented and interpreted in terms of plate tectonics.